Inter- and Intra-specific variation in egg size among reef fishes across the Isthmus of Panama - Robertson, D. Ross; Collin, Rachel (Frontiers in Ecology and Evolution, 2015)
Effects of planktonic food supplies and temperature on pelagic fish larvae are thought to be the primary environmental determinants of adaptive variation in egg size. Differences between the Atlantic and Pacific coasts of Panama in primary production (higher in the Pacific due to upwelling) and temperature (less seasonal in the non-upwelling Caribbean) allow testing such ideas. We compared the volumes, dry weights and energy content of eggs of 24 species of reef fishes from the two sides of the isthmus during the cool and warm seasons. Both egg volume and egg dry weight were good predictors of egg energy content among species, although not within species. Caribbean species produced larger eggs than their close relatives in the Pacific. In the Pacific, eggs were significantly larger during the cool upwelling season than during the warm, non-upwelling period, with a similar but weaker seasonal pattern evident in the Caribbean. The production of larger eggs in the low-productivity Caribbean is consistent with the hypothesis that species produce larger eggs and offspring when larval food supplies are lower. Parallel patterns of seasonal variation in eggs size and the greater strength of that relationship in the Pacific indicate that temperature drives seasonal variation in egg size within species. The decline in egg size with increasing temperature, a general pattern among ectotherms, may be a physiological side-effect, due to differing effects of temperature on various metabolic processes during oogenesis or on hormones that influence growth and reproduction. Alternatively, the seasonal pattern may be adaptive in these fishes, by affecting larval performance or maintaining a particular timeline of major events during embryonic development.